1983
DOI: 10.1063/1.445609
|View full text |Cite
|
Sign up to set email alerts
|

Reorientational motion, collision-induced scattering, and vibrational relaxation in liquid carbonyl sulfide

Abstract: Articles you may be interested inThe effects of vibrational mode and collision energy on the reaction of formaldehyde cation with carbonyl sulfide Dynamics of molecular reorientational motion and vibrational relaxation in liquids. ChloroformThe rotational and vibrational behavior of neat liquid carbonyl sulfide under its own vapor pressure is investigated through Raman line shape studies of the symmetric v I C = S stretching mode over the temperature range T = 183 to 303 K. The reorientational motion is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…:l value can be determined independently from the base The question posed is thus whether an acceptable value of n can be found where the signal to noise is large enough to provide a precise A value from the derivative function without sacrificing the accuracy of the A value obtained. In order to answer this question, we have taken derivatives of the anisotropic VI mode Raman line shapes of liquid OCS presented in an earlier publication 23 where the true base line was known. It was found that a reasonable range of n values did exist which could produce derivative functions that reproduced the true A values to within 10%.…”
Section: B V1 Mode Anisotropic Raman Line Shapementioning
confidence: 99%
“…:l value can be determined independently from the base The question posed is thus whether an acceptable value of n can be found where the signal to noise is large enough to provide a precise A value from the derivative function without sacrificing the accuracy of the A value obtained. In order to answer this question, we have taken derivatives of the anisotropic VI mode Raman line shapes of liquid OCS presented in an earlier publication 23 where the true base line was known. It was found that a reasonable range of n values did exist which could produce derivative functions that reproduced the true A values to within 10%.…”
Section: B V1 Mode Anisotropic Raman Line Shapementioning
confidence: 99%